An operational strategy for residential microgrids considering emergency power source functionality - LI Xianfeng; HU Chengang; BU Limin; MIAO Wenjie; HUANG Wenzhe; MA Jianjun (Zhejiang dianli, 2024)
As the societal demand for electricity rises and extreme weather events become more frequent， power interruptions are occurring， leading to a decline in the quality of electricity for users such as residential communities. In response to this issue， a study was conducted on the operational strategies of residential microgrids incorporating emergency power sources. Initially， a model for a residential microgrid incorporating emergency power sources was established， including distributed PV， energy storage， electric vehicles， and other control resources. Subsequently， in regular conditions， a risk assessment and energy pre-management strategy was proposed with the objective of minimizing electricity purchase costs and constraining energy storage. In the event of external power supply interruptions， while ensuring the normal supply of essential loads， an emergency energy management strategy was introduced with the goals of maximizing resource utilization and minimizing operational costs， using energy storage capacity as a constraint. Finally， the effectiveness of the proposed operational strategies was validated through simulation experiments simulating load interruptions in residential communities. This operational strategy effectively addresses power interruptions in residential communities， balancing the security and reliability of residential power supply while considering the utilization rate of emergency power resources and economic operational benefits.